A CONCEPTUAL MODEL FOR DESIGNING TEACHERS’ SELF-DIRECTED AND WELL-BEING-CENTERED PROFESSIONAL DEVELOPMENT - Starks, Francheska (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Research shows that educators often experience significant levels of stress in the workplace that impact their enthusiasm about the profession and longevity in the education field. Some personal impacts of stress on educators may include emotional numbing, feeling shut down, loss of energy, and increased illness or fatigue. Recently, some schools and districts have begun investing in programming to support educator well-being; however, these initiatives are rarely developed and co-led by educators themselves. The purpose of this paper is to introduce a research-based for designing and implementing educator-directed programming that seeks to support the well-being of K-12 educators. Implications for future research and practice are provided at the end of the paper.